La Impresión 3D como Alternativa de Construcción de Vivienda en Bucaramanga, Santander (2023)
13 Abstract This research focuses on the study of additive manufacturing, or 3D printing, in the construction industry in order to develop a technical study that shows it as a sustainable alternative for housing construction in Bucaramanga, Santander; This is done through the study of research and projects carried out worldwide that allow us to understand its operation to evaluate its viability in social technical-constructive, environmental, structural, time and cost aspects